Sustainable livestock development in Sudan: Challenges, opportunities, and policy priorities - Alfadul, Hanan; Siddig, Khalid; Ahmed, Mosab O. M.; Abushama, Hala; Kirui, Oliver K. (International Food Policy Research Institute, 2024)
Livestock in Sudan plays a crucial role in the national economy, particularly in alleviating poverty and enhancing food security. Despite its significance, the last comprehensive livestock census for the country was conducted in 1975, resulting in now outdated and often unreliable data. Recent estimates by USAID indicate that Sudan ranks among the top three African countries in terms of livestock numbers, with an estimated 105.6 million animals. The livestock population in Sudan is predominantly composed of camels, goats, sheep, and cattle. The spatial distribution of livestock is variable and influenced by local factors such as feed resources, land use, and ecological conditions. The Greater Kordofan and Greater Darfur regions have the largest livestock numbers. However, discrepancies between official statistics and field data show the need for updated and accurate livestock data. The livestock sector provides 40 percent of employment and 34 percent of Sudan’s agricultural gross domestic product (GDP). The livestock sector is a vital source of foreign exchange for the Sudanese economy through exports of livestock and livestock products. Besides its economic contributions, the livestock sector provides essential food products, including meat, eggs, and milk, and draught power for agricultural operations and transportation, particularly in rural areas. However, relative to irrigated agriculture, the sector faces challenges due to underinvestment and minimal government attention.